Exploring the viability of a floating photocatalyst in a continuous stirred tank reactor system for continuous water treatment - Yang, Heejin; Lee, Youn Jun; Park, Seong Jik; Lee, Chang Gu (Environmental Science and Pollution Research, 2023)
The use of photocatalysts in continuous stirred tank reactor (CSTR) systems allows for efficient and continuous water treatment, thus meeting the demand for scalable technology and comparative data in large-scale implementations. Hence, this study aims to explore the feasibility of a floating photocatalyst within a CSTR system for continuous water treatment. An expanded polystyrene (EPS)-TiO2 composite was synthesized following established methodologies, and their efficacy in removing the water pollutant methylene blue (MB) was compared for both batch and CSTR systems. A nonlinear first-order model was identified as the most suitable approach to accurately simulate MB degradation under experimental conditions, and the calculated pseudo-first-order degradation rate constant (kʹ) for the CSTR system (0.0126–0.0172/min) was found to be superior to that observed for the batch system (0.0113/min). In addition, an increase in the flow rate reduced the retention time, leading to lower MB removal efficiency for the CSTR system. In addition, the EPS-TiO2/UV system with a CSTR configuration was found to efficiently use light and energy based on the calculated quantum yield (Φ = 2.86 × 10–4) and electrical energy per order (EEO = 857.46 kWh/m3/order). The findings of this study contribute to the development of sustainable and efficient water treatment strategies, offering valuable insight into the implementation of practical water treatment processes.
Keywords: Bioreactors; Electricity; Titanium; Water Purification; Continuous stirred tank reactor; Expanded polystyrene; Floating photocatalyst; TiO2; Water treatment